The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3928/00485713-20160125-01
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances in Posttraumatic Stress Disorder: Updated Review and Implications for Treatment

Abstract: Sleep disturbances are common in adults with PTSD and range from insomnia and nightmares to periodic leg movements and disruptive nocturnal behaviors. Together these findings suggest profound disturbances in rapid eye movement (REM) and non-REM (NREM) sleep, although there is a lack of consensus regarding a distinct profile of objective sleep disturbances associated with PTSD. Prospective, longitudinal studies have established that sleep disturbances represent a risk factor for the development and course of PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
66
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 30 publications
2
66
0
4
Order By: Relevance
“…Regarding the temporal association between sleep disturbance and PTSD severity, studies have supported similar effects of sleep disturbance on PTSD symptomatology, as reported in the current study in both civilian and military populations (Breslau et al, 2004;Miller et al, 2017). It has also been proposed that treating sleep problems directly is beneficial for both civilians and military populations with PTSD (Brownlow, Harb & Ross, 2016;Koffel et al, 2016).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Regarding the temporal association between sleep disturbance and PTSD severity, studies have supported similar effects of sleep disturbance on PTSD symptomatology, as reported in the current study in both civilian and military populations (Breslau et al, 2004;Miller et al, 2017). It has also been proposed that treating sleep problems directly is beneficial for both civilians and military populations with PTSD (Brownlow, Harb & Ross, 2016;Koffel et al, 2016).…”
Section: Discussionsupporting
confidence: 84%
“…We were also unable to assess nightmare frequency or intensity in our cohort as our independent measure of sleep disturbance (i.e., the JSS did not include any nightmarerelated items). The prevalence of nightmares and their relation to PTSD severity and outcomes is an important and relatively unexplored topic for future research (Cox et al, 2017;Koffel et al, 2016;Miller et al, 2017). Finally, although we report on a high rate of prescriptions given for sedative-hypnotic drugs, we did not assess the use of other psychotropic drugs, such as benzodiazepines, tricyclic antidepressants, opiates, or nonprescription sleep aids.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations